تعدد الزوجات في الشريعة الإسلامية _الإباحة في ظل أحكام الشريعة ومقاصدها_ (مجلة الواحات للبحوث والدراسات, 2021)
Polygamy Is One Of The Issues That Provoked Much Controversy And Varied The Responses And Divergent Opinions Between Supporters, Opponents And Neutrals And Although The Islamic Sharia Has Been Stated In Its Rules And Purposes, The Attitude Towards Polygamy Has Been Governed By Social Habits Sometimes And By Ideologies Sometimes Other.Among Them And Those, The Invocation Of The Sharia To Return To Its Origins And Purposes In Regulating Polygamy Is The One That Sets The Record Straight, So That Polygamy Is Not Too Much And Is Not To Be Neglected. Polygamous Marriage Is A Social Phenomenon With Its Causes And Consequences, Which May Be A Necessity In Some Cases And May Not Be If It Is Not Regulated The Sharia And Did Not Achieve Its Purposes.This Paper Therefore Answers The Following Question:How Have The Rules Of Islamic Sharia Regulated Polygamy Through Texts And Purposes?